Fiction, experience and reality. What has film to do with life? - Zorroza, María Idoya (2022)
Films have been proposed as a method of evasion though audiovisual fictional narratives. The present paper analyses, from an anthropological stand of view, what does ‘fiction’ means, and what is its proper ‘type of reality’. In second place it focuses in its expressive and communicative character of the ‘human experience’, reason why it is understood and by which it also has a formative and enriching for the human being as ‘animal that creates and feeds from stories’. Finally, it focuses on the incidence of films on personal reality, concluding some elements of the non-immediate relation of films with the person’s radical life.